Perancangan Sistem Penjualan Dan Persediaan Spare Part Berbasis Web Pada Bengkel Mitra Motor - Nurhadi Surojudin1 (Teknik Informatika, Universitas Pelita Bangsa, 2018)
Responding to increasingly competitive competition in business, led to the idea of combining information technology with business. Virtual ordering illustrates a wide range of information technology, processes and practices in online business transactions without using manual transactions. By using online sales, companies can market a product or service to consumers with coverage throughout the world, so that in terms of business is a good opportunity to expand the market of products or services offered. This study aims to analyze and create a sales system application and supply of spare parts at a web-based motorcycle partner workshop that can present information needed by consumers. With this system, motorbike partner workshop parties can build a system for selling their products using the internet that can eliminate distance and time. The development tool used by the author is PHP as an application interface and MySQL as its database. This was all chosen because of its reliability in making web-based applications. The development method used is the Waterfall System Development Life Cycle (SDLC) with system modeling using UML (Unified Modeling Language). On this occasion, the author only discusses the ordering system through cash payments (both directly and via bank transfer) and the development of this web-based ordering system is only applied in the field of marketing and sales of motorcycle partner workshops.